Política estadual de educação especial no Espírito Santo : cartografando espaços locais - Vieira, Sônia Aparecida Alvarenga (2018)
This study aimed at mapping the active special education state politics, comprehending the schooling of students who are the target audience of special education in the state education network in the city of Cariacica/ES. The complexity experienced relates to concepts brought by Boaventura de Sousa Santos, such as: “Sociology of the Absences”, “Sociology of the Emergencies” and the concept of “Translation”, as well as theoretician-methodological precepts of the “symbolic cartography of the social representations”. In this perspective, the data collection occurred from September 2015 until December 2016, with collection of documents produced in the period of 2007 to 2016, to capture movements in small, medium and large scale. The map of active politics was modified according to the deepening of the research, bringing to light local, regional and global vicissitudes. The studies of Ball and Mainardes on the "Policy Cicle" collaborate with analyzes of policy in action and local articulations. The research dedicates more time for the medium-scale developments, at which point it was possible to monitor the actions of the SRE Cariacica. The data show the increase in the number of multifunctional resource rooms, with availability of the Federal Government's Accessible School Program, and the changes that occurred in the organisational forms of do special education in recent years. These results bring to the school the challenge of promoting access to the school curriculum to the target audience of special education. Although the current legislation emphasizes the inclusion of these students in common schools, one realizes that there are weaknesses in the policies introduced to support the schooling, the professional qualification and in the forms of care, as well as there is a mismatch between the policies on special education established by educational documents and those practiced in the common schools. Educational policies are a field of permanent construction and expansion. From the educational issues that emerged in this study, it was possible to identify a power in the service for the target audience students of special education: training actions carried out by the special education team of SRE Cariacica, geared for educators. The research discusses the management issues that have a direct relation with the acting of the specialized teacher, the advisory services conducted by the team of SRE Cariacica, the collaboration among the teachers in the school space, the design and the involvement of educators with the inclusion issues, the intersectoral actions, the relationship with the families. It is possible to understand that, when unveiling the fragilities of active policies, little by little they give place for new actions. This movement is presented as a transit of ideas that favors the perspective of a more democratic school.